2020
DOI: 10.3390/molecules25245926
|View full text |Cite
|
Sign up to set email alerts
|

Host-Guest Complexation of Oxaliplatin and Para-Sulfonatocalix[n]Arenes for Potential Use in Cancer Therapy

Abstract: P-sulfonatocalix[n]arenes have demonstrated a great potential for encapsulation of therapeutic drugs via host-guest complexation to improve solubility, stability, and bioavailability of encapsulated drugs. In this work, guest-host complexes of a third-generation anticancer drug (oxaliplatin) and p-4-sulfocalix[n]arenes (n = 4 and 6; p-SC4 and p-SC6, respectively) were prepared and investigated, using 1H NMR, UV, Job’s plot analysis, and DFT calculations, for use as cancer therapeutics. The peak amplitude of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 88 publications
(113 reference statements)
1
62
0
Order By: Relevance
“…Previous studies reported the direct relationship between the degree of the chemical shi of a guest molecule's protons and their depth of penetration inside the hollow cavity of the host molecule, designating the formation of host-guest inclusion complexes. 28,29,41,42 The most signicant upeld shi of $0.58 ppm was observed for the protons of the methyl groups bonded to the quaternary ammonium head of betaine, H c (Table 1 and Fig. S1 †) showing that they possessed the most signicant shielding effect.…”
Section: H Nmr Spectroscopymentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies reported the direct relationship between the degree of the chemical shi of a guest molecule's protons and their depth of penetration inside the hollow cavity of the host molecule, designating the formation of host-guest inclusion complexes. 28,29,41,42 The most signicant upeld shi of $0.58 ppm was observed for the protons of the methyl groups bonded to the quaternary ammonium head of betaine, H c (Table 1 and Fig. S1 †) showing that they possessed the most signicant shielding effect.…”
Section: H Nmr Spectroscopymentioning
confidence: 99%
“…The cell viability of either cancerous or non-cancerous cells was examined employing the SRB assay, and the IC 50 (in mg mL À1 ) was calculated using our methods described previously. 28,29,[32][33][34]…”
Section: Sulforhodamine B Colorimetric Assay (Srb)mentioning
confidence: 99%
See 3 more Smart Citations